A Test Strategy for Discriminating between Autocorrelation and Misspecification in Regression Analysis: A Critical Note - Knottnerus, Paul (The Review of Economics and Statistics, 1985)
Paul Knottnerus, A Test Strategy for Discriminating between Autocorrelation and Misspecification in Regression Analysis: A Critical Note, The Review of Economics and Statistics, Vol. 67, No. 1 (Feb., 1985), pp. 175-177